Legality of pre-trial data collection - Beglecovaitė, Gabija; Mikalajūnaitė, Rugilė (Vilnius University Open Series, 2024)
This article analyses the legality aspect of pre-trial investigation data. It discusses the concept of pre-trial investigation data, which reveals the importance and tasks of the pre-trial investigation stage. When examining the legality of pre-trial investigation data, it is important to take into account and ensure that the data collected comply with the requirements of the CPP and other legal acts. The pre-trial data collected forms the basis of the judicial proceedings and its legality and compliance with the law is therefore an essential element of a fair trial. Data obtained in accordance with the law is collected during the pre-trial phase of the investigation, but in certain cases it may be collected even before a pre-trial investigation has begun. This article sets out the necessary criteria and legislation to allow pre-trial data to become evidence. It highlights what needs to be taken into account when deciding on the probative value of information. It also analyses which methods of obtaining information do not contradict the criteria laid down in the law and what requirements are imposed on the participants in the proceedings and how the validity of the data can be checked. The final section of the article discusses examples of case law that present cases where pre-trial investigation data have been obtained illegally.
Keywords: pre-trial investigation data; collection of pre-trial investigation data; criminal procedure; legality